Learning and Using of Technical Terms in English For Non-Specialist Directions - Mamatkarimova B. Kh; Rakhmanova G.G (International Journal on Orange Technologies, 2021)
In this article is given the methods and difficulties of using technical terms for nonspecialist directions. There are different ways of learning and working on technical terms for specialists in their work. Education Technical English in high school is a separate aspect of the review of the system of teaching foreign languages in Uzbekistan.